Aplicación de técnicas de estudio para mejorar el rendimiento académico, de los niños y niñas del séptimo grado de educación general básica paralelo B, en el bloque 6 del área de lengua y literatura, de la unidad educativa Pompilio Reinoso Jaramillo del barrio Sauces Norte de la ciudad de Loja, período académico 2013 – 2014 - Vega Calva, Jessica Tatiana (2015)
This thesis entitled APPLICATION OF TECHNICAL STUDY TO IMPROVE THE ACADEMIC ACHIEVEMENT OF CHILDREN OF THE SEVENTH GRADE GENERAL BASIC EDUCATION PARALLEL B, in Block 6 AREA OF LANGUAGE AND LITERATURE, of the Education Unit "POMPILIO REINOSO JARAMILLO "DEL BARRIO NORTH WILLOW Loja, ACADEMIC PERIOD 2013-2014 with its overall objective to contribute to the implementation of study skills in the Area of Language Arts for students in seventh grade general education Basic parallel" B " Pompilio Education Unit Reinoso Jaramillo. The methods used for this research were: analytical, synthetic and as techniques used the survey of 19 students and a teacher, obtaining as results of research students if they have knowledge about study skills but they do an application the same as they use most are only what is underlined and summary Lacking greater insight into what a process on the implementation of the same as for example we take notes, underline, outline, implementation schemes and also You can make the use of chips for a better way to study. It is concluded that the application of model strategies by research by the method of workshop, directly benefited the students and teachers, helping to reduce the difficulties that students present when performing studies demonstrated through the Pearson r.